2007
DOI: 10.1124/mol.107.040964
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Binding Sites for Substrates and Modulators of Semicarbazide-Sensitive Amine Oxidases: Kinetic Consequences

Abstract: Human semicarbazide-sensitive amine oxidase (SSAO) is a target for novel anti-inflammatory drugs that inhibit enzymatic activity. However, progress in developing such drugs has been hampered by an incomplete understanding of mechanisms involved in substrate turnover. We report here results of a comparative study of human and bovine SSAO enzymes that reveal binding of substrates and other ligands to at least two (human) and up to four (bovine) distinct sites on enzyme monomers. Anaerobic spectroscopy reveals bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 35 publications
(68 reference statements)
4
36
0
Order By: Relevance
“…It is also consistent with very ancient findings indicating that the lipolytic response to this adrenergic drug was not differing when using albumins of different origin (human vs. bovine) in the incubation medium, while the potency of catecholamines (e.g., adrenaline) was different from one preparation to another [16]. Our current interpretation of such findings is that, in this period, albumin preparations were less purified than at the present time, and the bovine one was more contaminated by soluble amine oxidase, the activity of which is more abundant in bovine than in human plasma [14]. Consequently, the catecholamines were more oxidized in the former preparation and their lipolytic properties were altered, when compared to incubations with human albumin.…”
Section: Discussionmentioning
confidence: 92%
“…It is also consistent with very ancient findings indicating that the lipolytic response to this adrenergic drug was not differing when using albumins of different origin (human vs. bovine) in the incubation medium, while the potency of catecholamines (e.g., adrenaline) was different from one preparation to another [16]. Our current interpretation of such findings is that, in this period, albumin preparations were less purified than at the present time, and the bovine one was more contaminated by soluble amine oxidase, the activity of which is more abundant in bovine than in human plasma [14]. Consequently, the catecholamines were more oxidized in the former preparation and their lipolytic properties were altered, when compared to incubations with human albumin.…”
Section: Discussionmentioning
confidence: 92%
“…There is one structure of a non-covalently bound inhibitor of a mammalian CAO. Clonidine binds to BSAO in a solvent accessible pocket near the active site that forces the TPQ away from its active 'off-copper' conformation and into its 'on-copper' conformation (35). We have shown that clonidine is a weak inhibitor of hDAO.…”
Section: Discussionmentioning
confidence: 99%
“…Other purported activities of I2R ligands are related to the modulation of brain creatine kinase (B-CK)8 and semicarbazide-sensitive amino-oxidase (SSAO) 9. The physiological relevance of these molecular targets may suffice to explain the putative involvement of I2R in various diseases1012 including neuropathic and inflammatory pain 1316…”
Section: Introductionmentioning
confidence: 99%